Pengambilan Keputusan Kepala Sekolah Di SMP Negeri 2 Rupit Kabupaten Musi Rawas Utara - Sumarsih; Eni Hartati (Manajer Pendididikan, 2023)
The aim of the study was to analyze the decision making of the principal at SMP Negeri 2 Rupit, North Musi Rawas Regency. The research method uses a qualitative descriptive approach. Data collection techniques using observation, interviews and documentation. Data analysis techniques include the stages of data reduction, data presentation, verification and drawing conclusions. Check the validity of the data with persistence of observation and triangulation. The results of the study show that: The steps used by school principals in making decisions include identifying problems, compiling alternative solutions to problems, choosing the right alternatives, while decision-making techniques are carried out by considering the aspirations of subordinates, so that the results of joint decisions can be implemented as well as possible. Factors that influence school principals in making decisions include time availability, types of problems, student characteristics.